PENGARUH KUALITAS PELAYANAN DAN KEUNGGULAN BERSAING TERHADAP KEPUTUSAN NASABAH MENJADI NASABAH PADA KJKS BMT TARUNA SEJAHTERA CABANG BRINGIN KABUPATEN SEMARANG - Siti Rochmah; Fidyah Yuli Ernawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2019)
The purpose of this study is to find out the Service, Competitive Advantage partially or simultaneously to the Customer Decision to be a Customer at the KJKS BMT Taruna Sejahtera, Bringin Branch, Semarang Regency. The method used in this study is Multiple Regression Analysis. This research was conducted at the KJKS BMT Taruna Sejahtera, Bringin Branch, Semarang Regency.The results showed that Service Quality had a significant positive effect on Customer Decisions to Customers in the KJKS BMT Taruna Sejahtera Branch Semarang Regency, Competitive Advantage had a significant positive effect on Customer Decision to Become a Customer at KJKS BMT Taruna Sejahtera Bringin Branch Semarang Regency.